Evaluación de riesgos ergonómicos y su incidencia en la salud de los trabajadores del Gad Parroquial Rural Alluriquín en el 2016. Propuesta de un programa de prevención. UTC. Latacunga. 110 p. - Zambrano Medranda, Ludy Magdalena (2017)
In the present investigation, a study of the ergonomic risk factors for the GAD PARROQUIAL RURAL ALLURIQUÍN was carried out to design a prevention program. An identification of the most significant ergonomic risk factors were started using the matrix of the National Institute of Occupational Safety and Hygiene recommended by the Ministry of Labor, and then the RULA and RULA OFFICE method was used for the evaluation of jobs. We determined the exposure of all ergonomic risk factors detected as critical in the occurrence of musculoskeletal disorders to a targeted sample of a given population. The design of a prevention program; The product of this work determined measures of prevention of the aspects established as high risk in terms of: work content, space conditions, comfort of work and organizational factors using formats and structure recommended by Ecuadorian legislation and international standards.